Volumetric and Diffusion Abnormalities in Subcortical Nuclei of Older Adults With Cognitive Frailty - Wan, Mingyue; Xia, Rui; Lin, Huiying; Qiu, Pingting; He, Jianquan; Ye, Yu; Tao, Jing; Chen, Lidian; Zheng, Guohua (Frontiers in Aging Neuroscience, 2020)
Background Previous studies have revealed the degeneration of subcortical nuclei may contribute to neuropathological changes in the process of cognitive impairment. But it is unclear in cognitive frailty. The aim of this study is to investigate the changes of subcortical nuclei in older adults with cognitive frailty and their relationship with cognition decline and physical frailty. Methods A total of 26 older adults with cognitive frailty and 26 matched healthy subjects were enrolled. The cognitive function and physical frailty were assessed by using Montreal Cognitive Assessment (MoCA) scale (Fuzhou version) and Chinese version of Edmonton Frailty Scale(EFS). Volume and DTI parameters of subcortical nucleus were measured by using structural and diffusion tensor imaging brain MRI, and were compared between groups. Partial correlation analysis were conducted between subcortical nucleus volume, MoCA scores, and physical frailty indexs. Results Significant volume reduction was found in five subcortical nucleus including bilateral thalamus, left caudate, right pallidum and accumbens-area in older adults with cognitive frailty (P<0.05), and bilateral thalamus was most obvious. Decreased FA and RA values were observed only in the left thalamus in the CF group (P<0.05). No group differences were found in ADC value. MoCA scores was positively correlated with the volume of bilateral thalamus, right pallidum and accumbens area (P<0.05). While a negative correlation was found between physical frailty index and the volume of bilateral thalamus, caudate, pallidum and right accumbens area (P<0.05). Conclusion The microstructural changes occur in the subcortical nuclei of older adults with cognitive frailty, and these changes are correlated with cognition decline and physical frailty. Therefore the microstructural atrophy of the subcortical nuclei may involve in the pathological progression of cognitive frailty.